STRATEGI DAN TEKNIK PENGAJARAN BAHASA ARAB DENGAN METODE LANGUAGE IMMERSION - Sovinaz, Sovinaz; Setiyawan, Agung (STIQ Amuntai, 2023)
This research aims to understand strategies and techniques for teaching Arabic that a teacher can apply to learn Arabic using the language immersion method. Using this method, students can learn languages by interacting directly with the language environment in which they will learn them to learn how to speak, read, write, or listen directly. By collecting data from articles that discuss language immersion in language learning, researchers use a type of qualitative research with the nature of library studies that use books and scientific works as the object of study, which are then analyzed descriptively to produce a clear, systematic, objective, analytical, and critical discussion of strategies and techniques for teaching Arabic using language immersion. The results of the literature analysis show that strategies and techniques for teaching Arabic using the language immersion method effectively improve students' speaking, listening, reading, and writing skills. The key aspects of this method are the focus on active conversation, speaking practice, intensive listening exposure, reading and understanding of Arabic texts, and writing activities.